Computational linguistics : an international handbook on computer oriented language research and applications - Bátori, István S., 1935-; Lenders, Winfried, 1943-; Putschke, Wolfgang, 1937- (Berlin : Walter de Gruyter, 1989)
It was the late co-editor of the series "Handbücher zur Sprach- und Kommunikationswissenschaft", Gerold Ungeheuer, who was first to recognize the need for this handbook, and who committed himself to the all important inclusion in the series. The editors dedicate this volume to his memory.
Elektronická reprodukce.
Keywords: počítačová lingvistika; computational linguistics; studie; sborníky; příručky; e-knihy online; studies; papers of several authors; handbooks and manuals; e-books online